ANALYSIS OF MSMEs’ WEBSITE SERVICE QUALITY ON USER SATISFACTION USING WEBQUAL 4.0 METHOD - Iriani, Yani; Hartati, Verani; Setijadi; Ferdian, Rendiyatna (CENTRAL ASIA AND THE CAUCASUS, 2022)
The use of the internet as a marketing and selling medium has been increasing, nowadays. Hence, Micro, Small, and Medium Enterprises (MSMEs) also continue to strive in maximizing e-commerce facilities to compete. The MSMEs’ website is one of the tools that is constantly developed to help achieve customer satisfaction. The research aims to analyze the influence of website service quality on the satisfaction of MSMEs’ website users in Margasari Urban Village of Bandung. It is conducted by distributing questionnaires to 30 respondents. The study uses non-probability sampling with the type of convenience sampling. The data analysis technique applied is multiple linear regression. The WebQual 4.0 method is a method to determine the quality of a website based on public or user perceptions. The method consists of three categories, namely usability, information quality, and service interaction quality. The three categories are used as the reference in constructing the questionnaire to scrutinize the quality of the website. According to the results of data analysis, the variables consisting of usability, information quality, and service interaction quality have a significant effect on user satisfaction. The variable that greatly influences user satisfaction is the quality of information. Therefore, it is suggested to the website developer to improve the value of information quality both its navigations and appearance. With an attractive interface, the website will get a good first impression when users visit.